Ultrasound-guided intra-articular injection of hyaluronic acid and ketorolac for osteoarthritis of the carpometacarpal joint of the thumb: A retrospective comparative study - Koh, Sung Hoon (Medicine (Baltimore), 2019)
Intra-articular hyaluronic acid (HA) is widely used to treat symptomatic osteoarthritis (OA) in the carpometacarpal joint (CMCJ) of the thumb. However, although apparently effective and relatively safe, intra-articular HA injections act relatively slowly. Therefore, a nonsteroidal anti-inflammatory drug could be added for more prompt pain relief. The aim of this study was to compare the efficacy and safety of ultrasound (US)-guided intra-articular injection of HA and ketorolac with that of HA alone in patients with OA of the CMCJ of the thumb. Seventy-four patients identified by chart review to have a diagnosis of OA of the CMCJ of the thumb received either a US-guided intra-articular injection of 0.5 mL of sodium hyaluronate and 0.5 mL of ketorolac (n = 38) or 0.5 mL of sodium hyaluronate and 0.5 mL of saline (n = 36). Disabilities of the arm, shoulder, and hand (DASH) and verbal numeric scale (VNS) pain scores were recorded before and 1, 3, and 6 months after injection. Univariable analyses (using the chi-squared test) and multiple logistic regression analysis were performed to evaluate the relationship between potential predictors of the outcome (treatment allocation, patient age and sex, duration of pain, and Eaton–Littler classification) and therapeutic effects. The DASH and VNS scores were improved at 1, 3, and 6 months postinjection in both groups. The onset of pain relief was significantly more rapid (at 1 month) after the injection containing HA and ketorolac than after the injection containing HA alone. In 55.3% of cases, pain and function were improved postinjection compared with baseline and remained so for up to 6 months. The success rate was not significantly different between the assessments at 1, 3, and 6 months, and the univariable analyses did not identify any statistically significant potential predictors of the outcome. Multiple logistic regression analysis did not identify any independent predictors of a successful outcome at midterm follow-up. The onset of analgesic action was more rapid after an injection containing HA and ketorolac than after 1 containing HA alone in patients with OA of the CMCJ of the thumb. There were no serious complications.